Tunable phase gratings by wrinkling of plasma-oxidized PDMS: gradient skins and multiaxial patterns - Tan,A; Pellegrino,L; Cabral,JT (ACS Applied Polymer Materials, 2021)
Wrinkling instabilities in polymeric bilayers have been exploited as optical phase gratings with tunable performance. Here, we report strain modulated 1D and 2D phase gratings fabricated by the ubiquitous process of plasma-oxidation of polydimethylsiloxane (PDMS). While surface oxidation provides a remarkably facile glassy skin formation approach, minimizing delamination and debonding, it inherently results in a gradient conversion profile emanating from the top film interface. We examine and quantitatively model the consequences of this gradient layer on the optical properties of the resulting strain-tunable phase gratings. Diffraction efficiencies up to 48% are demonstrated. We then develop and validate a surface reconstruction methodology based on the diffraction pattern of our sinusoidal gratings and our model, which we extend to the high deformation regimes and to 2D gratings, obtained by superposition of two wrinkling generations, where both amplitudes and wavelengths can be independently tuned. Overall, this approach provides a rapid, robust and predictive framework for the design and fabrication of tunable, single, and multiaxial surface gratings.